Greening Soweto : calculating above-ground tree biomass, stored carbon and net economic value - Lembani, Reuben Lungu (My University, 2016)
Quantifying ecosystem services of urban forests has become an important subject for the national and international ecological economics agenda. This is in the wake of offsetting anthropogenic emissions of CO2, while promoting urban habitability and sustainability. This study estimates above-ground tree biomass, carbon stored and the associated economic value and net economic value of carbon sequestrated by the tree planting project in Soweto, Johannesburg, South Africa. Measurements of diameter at breast height (1.3 m) and tree height were done on all the individual trees that were recently planted (estimated to be about seven years) and other trees estimated to be over 25 years old in Petrus Molefe Park and Thokoza Park. A general allometric equation by Tietema (1993) was used to estimate above-ground biomass which was converted to carbon stocks. The economic value of carbon sequestrated was calculated at an equivalent price of R440.40 per tonne of carbon. The total above-ground biomass, carbon stored and economic value, and net economic value of the trees in Petrus Molefe Park was 7.45 tonnes, 3.35 tonnes, R1,475 and R-495,325, while the trees in Thokoza Park had 205.76 tonnes, 92.59 tonnes, R40,777 and R-312,023, respectively. The results indicated that the older trees in Thokoza Park had larger amounts of above-ground tree biomass, greater carbon storage and net economic value than the younger trees in Petrus Molefe Park. The economic values of carbon sequestrated were less than the cost of planting the trees, therefore the net economic value of carbon sequestrated were negative. The project is at an early, but promising stage, since the Greening Soweto Project provided a number of ecosystem services (i.e. beautifying the landscape, filtering air, recreation and amenity etc.), the performance of the project was evaluated by the extent to which it integrates the environmental and social benefits into the economic benefits and opportunities. Key words: Above-ground biomass, allometric equation, carbon stored, diameter at breast height, net economic value.
A research report submitted to the Faculty of Science, University of the Witwatersrand, in partial fulfillment of the requirement for the degree of Master in Environmental Science Johannesburg, 2015
Keywords: Ecosystem services.; Environmental management.; Biodiversity conservation.; Natural resources--Management--Economic aspects.; Ecosystem management--Economic aspects.; Agriculture--Environmental aspects.